Optical Switching of Robust Ferroelectric Polarization on Epitaxial Hf0.5Zr0.5O2 Integrated with BaTiO3 - Dong, Wenjing; Tan, Huan; Zou, Jingye; Quintana, Alberto; Song, Tingfeng; Magén, César; Cazorla, Claudio; Sánchez, Florencio; Fina, Ignasi (Nano-Micro Letters, 2026)
Optical switching of ferroelectric polarization is of interest for wireless and energy-efficient control of logic states. So far, this phenomenon has been widely demonstrated only in ferroelectric perovskites, while studies on other emerging ferroelectrics remain limited. In this regard, the paradigmatic example of a technologically relevant ferroelectric material is HfO2. However, HfO2 has a very wide bandgap, limiting light absorption. So far, the proposed strategies to enhance light absorption in HfO2-based systems are detrimental to ferroelectric properties, i.e., bandgap lowering or on-purpose defect introduction, which reduce switchable polarization and increase the presence of leakage currents. Here, we show that good ferroelectric properties, i.e., sizeable polarization (up to 15 μC cm−2), low leakage current (under 10–6 A cm−2), high endurance (up to 108 cycles) and fast switching (< 50 ns), can be achieved in epitaxial Hf0.5Zr0.5O2 films through an alternative strategy, BaTiO3 capping. While ferroelectric properties are remarkable, we demonstrate that the presence of BaTiO3 allows light absorption and the concomitant electric field generation, as supported by density functional theory calculations, which enables optical switching of polarization in Hf0.5Zr0.5O2 under 405 nm illumination. It is observed that optical switching is more efficient in films with thicker BaTiO3 capping layer. The high polarizability of BaTiO3 contributes to minimizing degradation in the ferroelectric response of the system. The results presented here indicate that appropriate designs can be followed to obtain optical switching of polarization in ferroelectric HfO2 while preserving main functional properties. Highlights: 1 Integration of perovskite BaTiO3 with epitaxial fluorite Hf0.5Zr0.5O2 is demonstrated. 2 Polarization up to 15 μC cm−2, leakage current densities below 10–6 A cm−2, endurance up to 108 cycles, and switching times shorter than 50 ns are achieved. 3 Remote optical switching of the polarization is demonstrated, and it is shown to be controlled by the thickness of the BaTiO3 capping layer.